The extramedical use and diversion of opioid substitution medications and other medications in prison settings in Australia following the introduction of buprenorphine–naloxone film. (1st September 2015) - White, Nancy; Ali, Robert; Larance, Briony; Zador, Deborah; Mattick, Richard P.; Degenhardt, Louisa
Abstract: Introduction and Aims: Around 65% of people incarcerated in prisons in Australia, America and Europe have a history of drug dependence, sometimes treated with opioid substitution treatment (OST) medications. Studies report that those in treatment in prison do engage in some level of diversion to others, whether on a voluntary or coerced basis. We aimed to examine the use of prescribed and non‐prescribed OST medications by those in prisons, especially buprenorphine–naloxone film (BNX‐F); the extent of non‐adherence and diversion and reasons for such practices; and the impact of the introduction of BNX‐F into the prison system. Design and Methods: Mixed methods study drawing on: (i) structured interviews with current OST clients ( n = 60) who reported being incarcerated in the 12 months prior to being interviewed and (ii) qualitative interviews with key experts working in corrections and prison (or justice) health settings. Results: The majority were prescribed OST medications in prison, with 25% removing all or part of their supervised dose on at least one occasion, and 44% reporting use of non‐prescribed medications. Some reported intravenous use (14% injected). One‐third of OST recipients reported selling/sharing OST medications with others in prison. The introduction of BNX‐F into the prison system saw different diversion methods used and removal from dosing within prison. Discussion and Conclusions: Despite prison being a highly regulated and controlled environment, some level of diversion and sharing of psychoactive medication occurs among prisoners. The buprenorphine formulations used in OST present particular challenges with respect to supervised dosing in this setting. [White N, Ali R, Larance B, Zador D, Mattick RP, Degenhardt L. The extramedical use and diversion of opioid substitution medications and other medications in prison settings in Australia following the introduction of buprenorphine–naloxone film. Drug Alcohol Rev 2015;●●:●●–●●]